2021
DOI: 10.1186/s13054-021-03668-5
|View full text |Cite
|
Sign up to set email alerts
|

Venoarterial extracorporeal membrane oxygenation as mechanical circulatory support in adult septic shock: a systematic review and meta-analysis with individual participant data meta-regression analysis

Abstract: Background While recommended by international societal guidelines in the paediatric population, the use of venoarterial extracorporeal membrane oxygenation (VA ECMO) as mechanical circulatory support for refractory septic shock in adults is controversial. We aimed to characterise the outcomes of adults with septic shock requiring VA ECMO, and identify factors associated with survival. Methods We searched Pubmed, Embase, Scopus and Cochrane databas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 57 publications
1
36
0
4
Order By: Relevance
“…Survival rates among patients with severely reduced left ventricular ejection fraction (<20%) were 62% in a recent meta-analysis. 3 …”
Section: Discussionmentioning
confidence: 99%
“…Survival rates among patients with severely reduced left ventricular ejection fraction (<20%) were 62% in a recent meta-analysis. 3 …”
Section: Discussionmentioning
confidence: 99%
“… 10 Despite the emerging use of VA ECMO for the treatment of SIC, 10 its use in adults with SIC is not as effective as in children with SIC. 11 The hemodynamic pattern of septic shock differs markedly across age groups: newborn infants typically present with pulmonary hypertension and right heart failure, young children with left heart failure, and adolescents and adults with distributive shock. 12 Recently, Ling et al .…”
Section: Discussionmentioning
confidence: 99%
“…The survival rates among patients with LVEF >35%, LVEF between 20% and 35%, and LVEF <20% were 32.1%, 42.3%, and 62.0%, respectively. 11 This means that a higher pre‐ECMO LVEF results in lower survival. In septic patients with preserved cardiac function, VA ECMO may be contraindicated due to decreasing cardiac output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective cohort study confirmed the survival improvement by using extracorporeal membrane oxygenation (ECMO) in the cohort with sepsis-induced cardiogenic shock [3], whereas a recent meta-analysis clarified that ECMO had rather worse outcomes in patients with septic shock without severely decreased cardiac function [4]. ECMO is considered a suitable treatment option in selected patients with severe sepsis-induced cardiogenic shock [2], although the optimal patient selection procedure requires further investigation.…”
Section: Introductionmentioning
confidence: 99%